A study of treatment patterns in symptomatic management of fever in children (antipyresis) among Pediatricians - V Benakanal, Shreeshail; S Kumar, Vikram; B. Patil, Ravindra (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: Fever is an extremely common sign in pediatric patients and the most common cause for a child to be taken to the doctor. There are no guidelines or consensus in India about symptomatic management of fever and hence there can be too many misconceptions and conflicting results about fever management. Aims: In this study the aim was to identify knowledge gaps of primary care doctors regarding fever in children. Methods: This cross-sectional study was conducted from August 2019 –October 2019 involving Pediatricians and family physicians (n=935). A questionnaire was administered to convenient samples of pediatricians and family physicians eliciting information about fever definition, methods of temperature measurement, and antipyretic use. Differences in responses between the doctors were evaluated. Results: The data was analyzed using the SPSS 16.0 program and descriptive statistics were used. In the present study 40% of the doctors knew that a body temperature of above 37.5°C according to an axillary measurement is defined as fever. Only 36% of the doctors took into consideration signs and symptoms other than fever to prescribe antipyretics. Almost 85% of the doctors prescribed antipyretics to control fever or prevent complications of fever especially febrile seizures. Most of the doctors (76.3%) in this study reported that the intensity of fever may be used as an indicator for severe bacterial infection. A great majority of doctors (65.3%) stated that they advised parents to alternate the use of ibuprofen and paracetamol. Conclusions: There were significant misconceptions about the management and complications of fever. There is a perceived need to improve the recognition, assessment, and management of fever with regards to underlying illnesses in children and a national consensus statement on fever and antipyresis in children.